The Strategy of the Islamic Studies Education Teacher in Teaching Multicultural Values to Establish an Attitude of Tolerance in SMA Yayasan Pandaan - Muhammad Sadad Fahmi; Ali Muhtarom; Achmad Yusuf (UMSU, 2023)
This study aims to explain the multicultural values developed at Yayasan Pandaan High School and the strategies used by PAI teachers to teach multicultural values to students. The research method used is qualitative with data collection through observation, interviews and documentation. The purpose of this study is to identify the multicultural values developed and the strategies used by PAI teachers in instilling multicultural values. The findings concluded that the multicultural values developed in Yayasan Pandaan High School are tolerance, cooperation and peace-loving. The strategies of PAI teachers in instilling multicultural values include the integration of multicultural values in PAI learning materials, methods and media. The inhibiting and supporting factors come from the school environment both externally and internally.